Changes in the coastline of the area extending from Misrata to Tripoli, study using geographic information systems and remote sensing techniques. (Journal of Libya for geographical studies, 2025)
This study aims to analyze the spatial and temporal changes of the coastline between the cities of Misrata and Tripoli, using Geographic Information Systems (GIS) techniques and remote sensing (RS). This study gains its importance from the vital role of coasts in supporting economic and tourism activities and protecting the natural environment, as well as coasts which considered as sensitive areas to any environmental and human changes.Multispectral and temporal satellite images were used to determine coastlines over a successive time periods, focusing on the years from 1977 to 2024. The study relied on image analyzed using ArcGIS programs in order to identify areas that were exposed to erosion and removal in addition to sedimentation. Satellite image correction techniques and digital elevation data analysis were also used to evaluate the impact of natural and human factors.The results obtained showed that the coastline examined have witnessed noticeable changes, some areas were subjected to severe erosion as a result of natural factors such as high waves and possibly due to climate changes.  Other areas have witnessed natural sedimentation or due to human interventions such as the construction of ports and coastal roads. The study have also indicated that unsustainable human activities, such as sand mining and urban sprawl were major factors in accelerating these changes.The study recommends developing coastal zone management strategies with the implementation of  a continues monitoring program using GIS and RS technologies, to trace any changes and also used as  planning tool for  sustainable protection measures that reduce the impact of coastal changes on infrastructure and the environment.
Keywords: coastline; Misrata; Tripoli; geographic information systems (GIS); remote sensing (RS); coastline changes; sculpting; sedimentation